TINJAUAN FATWA MUI NOMOR: 1/MUNAS VII/MUI/5/2005 TENTANG HAK KEKAYAAN INTELEKTUAL (HaKI) TERHADAP PRAKTIK JUAL BELI BUKU FOTOKOPI DI SINTANG - Susirawati Susirawati; Syahbudi Syahbudi; Arif Wibowo (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2022)
The main point of this research is that the cost of buying and selling photocopies in the city of Sintang, West Kalimantan.. In this context,